Alteraciones transversales del maxilar superior según lo establecido por el índice de mayoral de los estudiantes del colegio Adolfo Valarezo de la ciudad de Loja en el periodo marzo-agosto del 2015 - Borja Vicente, Maritza Lizette (2015)
One of the big problems that present in the odontology practice are all that have to see with the correct lineament and position of the teech of here that the purpose and the encourage of this job seach is knom if using, diferents medies between that we can named Moyers, Pont, Tanaka, Mayoral, etc To get establish a correct diagnostic; there by I`ve dediced choose to Indice of Mayoral and stablish if the measines propose by it is exactly iqual to obtain in a simple of so students of Adolfo Valarezo high school in Loja city. Made a clinic test of the students Adolfo Valarezo high school in Loja city of that included whole patients that had present in their mouths the firsts and second premolars and firsts super molar health and the correct position, obtain so patients both sex between 13 and 15 years old. Determined the distance understand between the forrows that separated the peak, vesticulars, and palatins of the first and second upper premolars and between the central nostrils where counverge the peakes of the first opper molars of which objectives is determine that of both alterations transverse the upper maxilar predomine in this group of study. The results obtained were that both sexes predomine the Macrognatismo transverse of maxilar. The shape of the upper arcades predomine the parabolice shape being 38% in men and 42% in women.